Generation of dark pulses in a bismuth tellurite based mode-locked erbium-doped fiber laser - Rosdin, Raja Zaimas Rosdin Raja; Paul, Mukul Chandra; Dhar, Anirban; Das, Shyamal; Harun, Sulaiman Wadi; Razak, N.F.; Yasin, Moh (National Institute R and D of Materials Physics, 2019)
We report on the formation of dark pulses in a highly nonlinear fiber laser passively mode-locked by a Bistmuth Tellurite (Bi2Te3) based SA. The SA was fabricated by embedding Bi2Te3 powder into polyvinyl alcohol (PVA) film by a solution casting technique. By inserting the SA into an EDFL cavity, stable mode-locked operation was achieved at 1592.68 nm with the maximum pulse energy up to 2.38 nJ by adjusting polarization controller. The laser operated at pulse repetition frequency of 1.0 MHz with a pulse width of 215 ns. These results suggested that Bi2Te3 could be developed as an effective SA for mode-locked dark pulses generation in a highly nonlinear cavity. © 2019, S.C. Virtual Company of Phisics S.R.L. All rights reserved.